Negara, Agama dan Demokrasi dalam Penegakan Hukum di Indonesia - Eny Apri Winarni (Balai Teknologi dan Komunikasi Pendidikan DIY, 2025)
Indonesia, which emerged as a country in the 20th century, has adopted the principle of a state of law that is in line with the principle of constitutionalism without abandoning the religious values held by the people of Indonesia. This can be seen from the consensus of the Indonesian people which is manifested in the 1945 Constitution, which is recognized as the country's constitution. This agreement then developed into a common goal known as the state philosophy or staatsidee (state ideals). Democracy, Religion and the rule of law are three concepts that are interrelated and cannot be separated. In the framework of democracy there is the principle of people's sovereignty (democratie), in religion there are absolute values of truth while in the concept of the rule of law there is the principle of the rule of law (nomocratie). The institutional mechanism in a state of law must be able to protect the rights of citizens from injustice by prioritizing the principles of humanity and mutual respect for the continuity of applicable law. This mechanism is an integral part of the legal system and its law enforcement officers. Indonesia as a democratic state of law, supports the principle of people's sovereignty and the principle of a state of law based on the religious teachings of itspeople.